Pemanfaatan Wireless Aplication Sebagai Perangkat Untuk Mengakses Web Address - Sony Oktapriandi (MANAJEMEN INFORMATIKA, 2010)
Now internet is a very important information media beside TV and radio. In the internet there are a lot of infortant informations, it’s from entertainment information, education, technology, etc. In order to the user can used internet in the PC (personal computer) so they need a modem as conected media a computer with internet. In the internet there are some web address wich can search with used keyboard and mouse as the media. Searching a web address the user just typing the address of the website, but it is very rarely if somebody opened web address at internet with used a remote control. It is cause remote control used for subtitudes media witch on/off at the TV screen. Opened a web addres, the user of remote control have the more superior equal with typing the web address. The superior of the remote control is the user just pressure the butto on the remote for opened website address.